Natural Shape-Retaining Microcapsules With Shells Made of Chitosan-Coated Colloidal Lignin Particles - Zou, Tao; Sipponen, Mika H.; Österberg, Monika (Frontiers in Chemistry, 2019)
Thin film coating of charged nanoparticles with oppositely charged polymers is an efficient and straightforward way for surface modification, but synthetic polyelectrolytes should be replaced by abundant biopolymers. In this study a thin film of chitosan was adsorbed onto colloidal lignin particles (CLPs) that were then systematically studied for olive oil stabilization with an objective to develop shape-retaining microcapsules that comprised of only renewable biomaterials. Full surface coverage was achieved with merely 5 wt% of chitosan relative to the dry weight of CLPs, reversing their surface charge from negative to positive. Such modification rendered the chitosan-coated particles excellent stabilizers for forming Pickering emulsions with olive oil. The emulsion droplets could be further stabilized by sodium triphosphate that provided ionic intra- and inter-particle cross-linking of the chitosan corona on the CLPs. Following the optimum conditions, the non-cross-linked microcapsules exhibited a strong stability against coalescence and the electrostatically stabilized ones additionally retained their shape upon drying and rewetting. Non-cross-linked microcapsules were used to demonstrate encapsulation and rapid release of ciprofloxacin as a model lipophilic drug in aqueous media. Overall, the combination of antimicrobial chitosan and antioxidative lignin nanoparticles hold unprecedented opportunities as biocompatible and biodegradable materials for controlled drug delivery.